2013
DOI: 10.4103/0973-1482.126452
|View full text |Cite
|
Sign up to set email alerts
|

Oral squamous cell carcinomas in age distinct population: A comparison of p53 immunoexpression

Abstract: The alteration rates were found to be slightly higher in older patients although not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Interestingly, a high frequency of p53 positivity was observed in TSCC of young patients even in the absence of TP53 mutations . In two recent studies, p53 expression was more frequent in OSCC of older patients than in younger patients . However, an opposite result was reported by Adduri et al and Siegelmann‐Danieli et al that observed a higher expression in young individuals.…”
Section: Genetic Alterationsmentioning
confidence: 86%
See 2 more Smart Citations
“…Interestingly, a high frequency of p53 positivity was observed in TSCC of young patients even in the absence of TP53 mutations . In two recent studies, p53 expression was more frequent in OSCC of older patients than in younger patients . However, an opposite result was reported by Adduri et al and Siegelmann‐Danieli et al that observed a higher expression in young individuals.…”
Section: Genetic Alterationsmentioning
confidence: 86%
“…18 The immunoexpression of p53 has been used as a marker for TP53 mutation in OSCC. 3,21,22 Interestingly, a high frequency of p53 positivity was observed in TSCC of young patients even in the absence of TP53 mutations. 21 In two recent studies, p53 expression was more frequent in OSCC of older patients than in younger patients.…”
Section: Genetic Alterationsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, many cases of squamous cell carcinoma lately are also found in young adults associated with those risk factors. 3 Squamous cell carcinoma in oral cavity will have a poor prognosis when found in an advanced stage, in which most patients die within 5 years after the enforcement of diagnosis. 3 Prognosis of oral cavity squamous cell carcinoma actually depends on histopathological grading and clinical staging of p53 gene is a tumor suppressor gene that plays an important role in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, p53 expressions were quantitatively categorized based on the percentage of positive tumor cells into score 1 if positive cells less than 25%, score 2 if positive cells between 25-50%, score 3 if positive cells between 51-75%, and score 4 if positive cells more than 75% with cut-off levels of <25% to >75%. 3,7 On the other hand, the intensity of p53 expressions are categorized based on color into score 1 for weak intensity (light brown), score 2 for moderate intensity (chocolate between score 1 and score 3), and score 3 for stronger intensity (dark brown). 8 Based on the percentage and intensity of the p53 expressions, the values of p53 expressions were calculated by multiplying the percentage value of p53 expressions (score 1, 2, 3 or 4) with the intensity of the p53 expressions (score 1, 2 or 3).…”
Section: Methodsmentioning
confidence: 99%